A new model for knowledge management: It's not what you know, but how you share it. Issue 6 (11th May 2015) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – We are, as we are constantly reminded, in a knowledge economy, and as such are liable to succumb to different market forces and variations than in previous paradigms. However if this is true, there is a central irony to our development of business activities in this area, in that there seems to be somewhat of a vacuum of knowledge about the knowledge economy. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.